We will discuss about the hyperbola of the ellipse along with the examples.

The centre of a conic section is a point which bisects every chord passing through it.

Definition of the centre of the hyperbola:

The mid-point of the line-segment joining the vertices of an hyperbola is called its centre.

Suppose the equation of the hyperbola be \(\frac{x^{2}}{a^{2}}\) - \(\frac{y^{2}}{b^{2}}\) = 1 then, from the above figure we observe that C is the mid-point of the line-segment AA', where A and A' are the two vertices. In case of the hyperbola \(\frac{x^{2}}{a^{2}}\) - \(\frac{y^{2}}{b^{2}}\) = 1, every chord is bisected at C (0, 0).

Therefore, C is the centre of the hyperbola and its co-ordinates are (0, 0).

Solved examples to find the centre of an hyperbola:

**1.** Find the co-ordinates of the centre of the hyperbola 3x\(^{2}\) - 2y\(^{2}\) - 6 = 0.

**Solution:**

The given equation of the hyperbola is 3x\(^{2}\) - 2y\(^{2}\) - 6 = 0.

Now form the above equation we get,

3x\(^{2}\) - 2y\(^{2}\) - 6 = 0

⇒ 3x\(^{2}\) - 2y\(^{2}\) = 6

Now dividing both sides by 6, we get

\(\frac{x^{2}}{2}\) - \(\frac{y^{2}}{3}\) = 1 ………….. (i)

This equation is of the form \(\frac{x^{2}}{a^{2}}\) - \(\frac{y^{2}}{b^{2}}\) = 1 (a\(^{2}\) > b\(^{2}\)).

Clearly, the centre of the hyperbola (1) is at the origin.

Therefore, the co-ordinates of the centre of the hyperbola 3x\(^{2}\) - 2y\(^{2}\) - 6 = 0 is (0, 0)

**2.**
Find the co-ordinates of the centre the hyperbola 5x\(^{2}\) - 9y\(^{2}\)
- 10x + 90y + 185 = 0.

**Solution: **

The given equation of the hyperbola is 5x\(^{2}\) - 9y\(^{2}\) - 10x - 90y - 265 = 0.

Now form the above equation we get,

5x\(^{2}\) - 9y\(^{2}\) - 10x - 90y - 265 = 0

⇒ 5x\(^{2}\) - 10x + 5 - 9y\(^{2}\) - 90y - 225 - 265 - 5 + 225 = 0

⇒ 5(x\(^{2}\) - 2x + 1) - 9(y\(^{2}\) + 10y + 25) = 45

⇒ \(\frac{(x - 1)^{2}}{9}\) - \(\frac{(y + 5)^{2}}{5}\) = 1

We
know that the equation of the hyperbola having centre at (α, β) and major and minor axes parallel to x and y-axes
respectively is, \(\frac{(x - α)^{2}}{a^{2}}\) - \(\frac{(y - β)^{2}}{b^{2}}\) = 1.

Now, comparing equation \(\frac{(x - 1)^{2}}{9}\) - \(\frac{(y + 5)^{2}}{5}\) = 1 with equation \(\frac{(x - α)^{2}}{a^{2}}\) - \(\frac{(y - β)^{2}}{b^{2}}\) = 1 we get,

α = 1, β = - 5, a\(^{2}\) = 9 ⇒ a = 3 and b\(^{2}\) = 5 ⇒ b = √5.

Therefore, the co-ordinates of its centre are (α, β) i.e., (1, - 5).

**● ****The ****Hyperbola**

**Definition of Hyperbola****Standard Equation of an Hyperbola****Vertex of the Hyperbola****Centre of the Hyperbola****Transverse and Conjugate Axis of the Hyperbola****Two Foci and Two Directrices of the Hyperbola****Latus Rectum of the Hyperbola****Position of a Point with Respect to the Hyperbola****Conjugate Hyperbola****Rectangular Hyperbola****Parametric Equation of the Hyperbola****Hyperbola Formulae****Problems on Hyperbola**

**11 and 12 Grade Math**__From Centre of the Hyperbola____ to HOME PAGE__

**Didn't find what you were looking for? Or want to know more information
about Math Only Math.
Use this Google Search to find what you need.**

## New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.